2011
DOI: 10.1080/15287394.2011.550566
|View full text |Cite
|
Sign up to set email alerts
|

Water Column Monitoring of the Biological Effects of Produced Water from the Ekofisk Offshore Oil Installation from 2006 to 2009

Abstract: The Norwegian water column monitoring program investigates the biological effects of offshore oil and gas activities in Norwegian waters. In three separate surveys in 2006, 2008, and 2009, bioaccumulation and biomarker responses were measured in mussels (Mytilus edulis) and Atlantic cod (Gadus morhua) held in cages at known distances from the produced water (PW) discharge at the Ekofisk oil field. Identical monitoring studies performed in all three years have allowed the biological effects and bioaccumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…After 30 days caging of mussels at the Cecina estuary in Tyrrhenian coast, twofold increase of MN incidences in gill cells has been observed (Nigro et al, 2006). The gradient-related increase in MN was found in haemocytes of mussels and liver erythrocytes of Atlantic cod caged for 5-6 months at Norwegian oil platforms in the North Sea (Hylland et al, 2008, Brooks et al, 2011. Furthermore recovery was detected in the Haven oilship sinking zone using the MN test in caged mussels ten years after the oil spill (Bolognesi et al, 2006b).…”
Section: Assessment Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 days caging of mussels at the Cecina estuary in Tyrrhenian coast, twofold increase of MN incidences in gill cells has been observed (Nigro et al, 2006). The gradient-related increase in MN was found in haemocytes of mussels and liver erythrocytes of Atlantic cod caged for 5-6 months at Norwegian oil platforms in the North Sea (Hylland et al, 2008, Brooks et al, 2011. Furthermore recovery was detected in the Haven oilship sinking zone using the MN test in caged mussels ten years after the oil spill (Bolognesi et al, 2006b).…”
Section: Assessment Criteriamentioning
confidence: 99%
“…Increased environmental genotoxicity and cytotoxicity has been described in an offshore Ekofisk oil extraction field (Rybakovas et al, 2009). The Water Column Monitoring Programme indicated increased genotoxicity in caged mussels in sites that were close to the Ekofisk oil platform indicating the ability to pinpoint source discharges with genotoxic endpoints in caged mussels (Baršienė, IRIS WCM Reports 2006Brooks et al, 2011). Significant MN elevation in fish and mussels was found after exposure to the crude oil extracted from the North Sea Bolognesi et al, 2006;Baršienė, Andreikėnaitė, 2007;Andreikėnaitė, 2010) and from arctic zones (Baršienė et al, unpublished data).…”
Section: Assessment Criteriamentioning
confidence: 99%
“…The estimated concentrations of PAH in seawater in the Potiguar Basin were comparable to the results found in the Norwegian sector of the North Sea (20-40 ng L −1 ), where blue mussels (Mytilus edulis) and SPMD were also used to estimate PAH concentrations in seawater (Utvik et al 1999;Durell et al 2000Durell et al , 2006Neff et al 2006;Brooks et al 2011a, b).…”
Section: Pah Concentrations In Spmdsmentioning
confidence: 90%
“…M. edulis has been used for biomonitoring studies in Norway (Aarab et al 2004(Aarab et al , 2008(Aarab et al , 2011; a suite of different biomarkers on their natural populations revealed differences between a previous aluminum smelter (encumbered by PAH) and a reference site. Furthermore, a real-time evaluation of a treatment system installed on an oil exploitation platform was made possible with the use of NR retention time and MN formation in sentinel M. edulis mussels (Brooks et al 2011;Sundt et al 2011).…”
Section: Limits Of Detectionmentioning
confidence: 99%